Meta-Analysis and Systematic Review: Risk Factors of Measles Incidence in Indonesia (2012 – 2021) - Fairuz Haniyah Ramadhani; R Azizah; Juliana Jalaludin; Santi Martini; Lilis Sulistyorini (Jurnal Kesehatan Masyarakat, 2023)
Measles is a highly contagious disease caused by the morbillivirus. According to WHO data, measles is one of the worldwide leading causes of death in children and infants. Indonesia is one of the ten countries with the most significant measles cases worldwide. Cases in Indonesia have increased due to a decrease in immunization coverage in Indonesia during the pandemic.  Besides low immunization coverage, other factors that influence the incidence of measles in Indonesia are nutritional status, mother’s knowledge, and occupancy density. This study aims to analyze the risk factors of immunization status, nutritional status, Mother’s knowledge, and occupancy density for measles in Indonesia.  This study used a meta-analysis method. The data sources used are Google Scholar, Pubmed, and Science Direct, from 2012-2021. The research articles found in this study are 148 articles. The report is then selected by screening to choose the year and research method and continued selection using inclusion criteria. Thus, the articles analyzed in this article are 23 research articles. The results showed that the variable immunization status, nutritional status, Mother knowledge, and occupancy density have risk factors for the incidence of measles in Indonesia. The result of measuring the pooled OR value sequentially from immunization status, nutritional status, mother’s knowledge, and occupancy density is e1.26=3.53; e0.72= 2.05; e1.36= 3.82;  e1.34= 3.89. The variable with the highest risk factor value for measles incidence in Indonesia is the occupancy density, followed by the Mother’s knowledge; immunization status; and nutritional status.